1997
DOI: 10.1021/jp972477b
|View full text |Cite
|
Sign up to set email alerts
|

Sonoluminescence from Aqueous Alcohol and Surfactant Solutions

Abstract: The sonoluminescence generated in water with pulsed 515 kHz ultrasound has been studied in the presence of different chain length (C1−C5) aliphatic alcohols and the surfactants sodium dodecyl sulfate (SDS), dodecyltrimethylammonium chloride (DTAC), and N-dodecyl-N,N-dimethyl-3-ammonio-1-propanesulfonate (DAPS). The ultrasound pulse widths used ranged from 1 to 10 ms, with duty cycles (on/off ratios) of 1:3 to 1:9. It was found that the sonoluminescence from the initial pulses was very low but increased in inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
270
3
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(315 citation statements)
references
References 20 publications
38
270
3
4
Order By: Relevance
“…The resistance to mass transfer has been shown to be surfactant concentration dependant; 10 mM as opposed to 1 mM of DTAC presents an increase in resistance [141]. It has been found that as the alkyl chain length of the surfactant increases the amount of solute able to be adsorbed at the surface decreases [231]. Therefore the degree to which the surfactant is able to be adsorbed at the surface of the bubble presents a limiting factor rather than the concentration of solute in the solution [215].…”
Section: Surfactantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The resistance to mass transfer has been shown to be surfactant concentration dependant; 10 mM as opposed to 1 mM of DTAC presents an increase in resistance [141]. It has been found that as the alkyl chain length of the surfactant increases the amount of solute able to be adsorbed at the surface decreases [231]. Therefore the degree to which the surfactant is able to be adsorbed at the surface of the bubble presents a limiting factor rather than the concentration of solute in the solution [215].…”
Section: Surfactantsmentioning
confidence: 99%
“…It was suggested that by using a highly charged surfactant bubbles would not be able to reach minimum size due to repulsions at the surface, however this was not apparent during experimentation [229]. Alcohols (especially with a terminal hydroxyl group) act in a similar vein to SDS with their nonpolar and polar surface properties reducing coalescence and increasing the number of active bubbles [31,47,231]. Tronson et al found that water solutions containing certain aliphatic alcohols quenched sonoluminescence at 515 kHz but indicated that by choosing the correct frequency it would be possible to increase sonochemical reactions [48].…”
Section: Surfactantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, non-volatile and hydrophobic molecule will undergo mainly radical attacks at the cavitation bubble interface (Ashokkumar et al 1997Barbour et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The modifications to the instrument allowed the delivery of pulsed ultrasound with a variable pulse-on time between 0.1 and 25 ms and pulse-off time between 0.8 ms and 6 s. The reactor was placed in a light-shielded housing, which also contained an end-on photomultiplier (Hamamatsu) for recording the SL from the insonated solutions (Ashokkumar et al 1997).…”
Section: Sonoluminescence Methodsmentioning
confidence: 99%